2006
DOI: 10.2118/84080-pa
|View full text |Cite
|
Sign up to set email alerts
|

Using Streamline-Derived Injection Efficiencies for Improved Waterflood Management

Abstract: Summary This paper describes a novel approach to predict injection- and production-well rate targets for improved management of waterfloods. The methodology centers on the unique ability of streamlines to define dynamic well allocation factors (WAFs) between injection and production wells. Streamlines allow well allocation factors to be broken down additionally into phase rates at either end of each injector/producer pair. Armed with these unique data, it is possible to define the injection e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 18 publications
0
58
0
2
Order By: Relevance
“…The streamline-based simulation workflow used for computing well allocation factors (WAFs) and injection efficiencies was proposed by Thiele and Batycky (2006). These efficiencies were used to optimize oil recovery by effectively reallocating water available for injection.…”
Section: Introductionmentioning
confidence: 99%
“…The streamline-based simulation workflow used for computing well allocation factors (WAFs) and injection efficiencies was proposed by Thiele and Batycky (2006). These efficiencies were used to optimize oil recovery by effectively reallocating water available for injection.…”
Section: Introductionmentioning
confidence: 99%
“…This allocation is rather simplistic that ignores deviations due to the heterogeneity in the reservoir. If the heterogeneity and connectivity in the reservoir can be well-defined, a more accurate set of allocation factors of the produced volumes could be determined through methods such as 3D streamline simulation (Thiele and Batycky, 2006). Figure 4 illustrates the allocation process for inverted water-injection patterns:…”
Section: Legendmentioning
confidence: 99%
“…This allows decoupling of the transport problem into a sum of 1D problems along streamlines. Previous studies have shown that streamline methods can predict the global sweep of water floods in heterogeneous reservoirs effectively (see, for example, Thiele and Batycky (2006)). A preliminary extension of streamline methods to compositional simulation was discussed in Thiele et al (1997).…”
Section: Existing Solversmentioning
confidence: 99%